The Effect of Green Color Therapy for Sleep Quality in Elderly in the Elderly Social Institution of Wana Seraya Denpasar - Dian Sari Putu Ita Purwanti (Coping: Community of Publishing in Nursing, 2013)
The increasing age of the elderly will experience a variety changes including in sleep quality which is can affected decreased quality of life. It is require treatment to overcome sleep disorder. There are many treatments of overcome sleep disorder; one of them is the green color therapy. The green color therapy can stimulate the pituitary in issuing various neurohormones that can influence sleep quality. This study aims to determine the therapeutic effect of green color on sleep quality in elderly in the Elderly Social Institution of Wana Seraya Denpasar. This research is a quasy-experimental study (pre-test and post-test with control group design). Samples consist of 30 elderly people that selected by purposive sampling, divided into control group and experimental group. The experimental group was given green color therapy for 10 minutes every day for seven days. The measuring of sleep quality was conducted by using The SMH (St. Mary's Hospital) Sleep Questionnaire which has been tested the validity and reliability. The result of study present that decrease of sleep quality score in control group is 1,60, whereas in the experimental group gained the decrease of sleep quality score is 6.20. Based on the independent sample t-test, the difference was statistically significant, with t value of 5,083 and p of 0,000, which means there is a therapeutic effect of green color therapy for sleep quality in elderly in the Elderly Social Institution of Wana Seraya Denpasar. Based on the results of this study green color therapy can be used as a therapeutic modality to improve sleep quality in elderly.Key words: elderly, sleep quality, green color therapy